REPRESENTASI BUDAYA DALAM IKLAN (ANALISIS SEMIOTIKA ROLAND BARTHES DALAM IKLAN KUKU BIMA ENER-G) VERSI NUSA TENGGARA TIMUR - Elves Jose Zulmiro (Universitas Pendidikan Nasional, 2017)
ABSTRACTKuku Bima Ener-G advertising on East Nusa Tenggara version is narrate life, and culture of East Nusa Tenggara people starting from living as farmer, weaving, culture of everyday life and pasola of society which not yet influenced by modern life and also authenticity of typical culture and unique which have to remain to be taken care of and preserve by router generation. This research is done through every scene in adverstiment of Kuku Bima Ener-G East Nusa Tenggara version. Method in this research is descriptive qualitative method, that’s because this research aim to know in detail somethings or causes influencing something. The result of this research found that denotation meaning at all checked adverstimenet of Kuku Bima Ener-G East Nusa Tenggara version scene to be concluded that denotation meaning given by the picture to us is about culture which still very jell situation in life of East Nusa Tenggara society, as a whole because living system which still traditional, and the culture system in the field of art, used by technology and equipments still very simple and also religion system had by still stick at late one who have passed away. From myth data analysis, the entire adverstimenet of Kuku Bima Ener-G Nusa Tenggara Timur version scene can be concluded that culture shall be expressed in everyday life such as gotong royong, farming, social life with each other and people’s life after death.Keywords : Culture Representation, Advertisement, Roland Barthes Semiotic